2014
DOI: 10.1007/s00167-014-3232-x
|View full text |Cite
|
Sign up to set email alerts
|

Open surgical treatment for chronic midportion Achilles tendinopathy: faster recovery with the soleus fibres transfer technique

Abstract: Prospective comparative study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
(94 reference statements)
0
14
0
Order By: Relevance
“…The majority of shoulder pain is associated with rotator cuff tendinopathy (RCT) [ 2 , 3 ]. Tendon pain is more common in people with rotator cuff tears than those with normal tendons [ 4 ], however there is a poor association between the severity of symptoms and extent of structural change [ 5 , 6 ] and current non-operative strategies are focused on steroid-based therapies with mixed results. There is a need to better understand the role of the peripheral tissue in tendinopathy-related pain to inform novel therapeutic options, possible pathways involve the glutaminergic and inflammatory systems [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of shoulder pain is associated with rotator cuff tendinopathy (RCT) [ 2 , 3 ]. Tendon pain is more common in people with rotator cuff tears than those with normal tendons [ 4 ], however there is a poor association between the severity of symptoms and extent of structural change [ 5 , 6 ] and current non-operative strategies are focused on steroid-based therapies with mixed results. There is a need to better understand the role of the peripheral tissue in tendinopathy-related pain to inform novel therapeutic options, possible pathways involve the glutaminergic and inflammatory systems [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies using open debridement techniques reported reasonable outcomes but wound complications have been a concern, especially when the angiosomal pattern of the posterior heel was not respected. A recent comparative study found superior outcomes when a transfer of soleus muscle bellies into the debrided Achilles tendon was added 86. Alfredson reported success in the use of ultrasound-guided small incision for the release of Achilles tendon from the ventral soft tissue in 519 patients with the recurrence rate of 5% 87.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly high complication rates were observed in studies evaluating the outcome of multiple tenotomies via an open procedure [4, 18, 21]. …”
Section: Discussionmentioning
confidence: 99%